The Role Of Social Media As Social Support For Postpartum Depression: Using Vosviewer Map For Bibliometric Review Analysis - Citra Purwanti; Faridah Moh Said; Syarifah Shafinaz (Fakultas Kesehatan IKesT Muhammadiyah Palembang, 2023)
Background : Postpartum period is a time of physiological changes for recovery from pregnancy, and also a psychological transition in which women gain competence and confidence in their role as mothers. The most significant factor on the development of maternal competence is social support. Today's widely accepted sources of social support are various social media platforms. To overcome this gap, this research uses VOSviewer to analyze text data from publications or reports related to the role of social media. Methods: This research was conducted by making maps based on text data. The first step, the researcher uses publish or perish to search using Google Scholar journal data related to social media as social support for postpartum depression from 2018 to 2022. The second step uses VOSviewer to create maps based on text data from reference managers with field titles and binary calculations as methods. For the third step, the researcher chose a threshold with a minimum number of occurrences of 3 terms, and the researcher found 1996 terms, 56 meet the threshold. From 56 meet of the treshhold, 34 number terms are selected. Results and Discussion : On July 13, 2023, there were 86 articles analyzed and the researchers found 4 clusters, cluster 1 had 11 items, cluster 2 had 10 items, cluster 3 had 9 items adn cluster 4 had 4 items. From the 3 clusters, three visualizations were obtained consisting of network, overlay and density visualization. Conclusion : Results mapping based on keywords social media as social support for postpartum mother. Most of the research on trial has been done. The data map of the network visualization social media as social support for postpartum depression is a review.